Luteolin Inhibits Breast Cancer Development and Progression In Vitro and In Vivo by Suppressing Notch Signaling and Regulating MiRNAs - Dawei Sun; He-Da Zhang; Ling Mao; Changfei Mao; Wei Chen; Meng Cui; Rong Ma; Haixia Cao; Chang-Weng Jing; Zhuo Wang; Jian Wu; Jinhai Tang (2015)
Background/Aims: This study aims to investigate the effect of Luteolin on breast cancer in vitro and in vivo and the interaction between miRNAs and Notch signaling after Luteolin intervention, and illustrates the possible underlying mechanism and regulation loop. Methods: Cell growth/survival assays and cell cycle analyses were performed to evaluate cell survival in vitro. Scratch tests, cell invasion assays and tube formation assays were carried out to analyze cell viability and identify the impact of Luteolin on angiogenesis. Critical components in the Notch pathway including proteins and mRNAs were detected by Western blotting analyses, ELISA assays and real-time reverse transcription-polymerase chain reaction. Matrix metalloproteinases activity was evaluated by gelatin zymography analyses. MiRNAs were analyzed by miRNA expression assays. After MDA-MB-231 cells were separately transfected with Notch-1 siRNA/cDNA and miRNA mimics, the above assays were also carried out to examine potential tumor cell changes. Xenograft models were applied to evaluate the treatment potency of Luteolin in breast cancer. Results: Luteolin significantly inhibited breast cancer cell survival, cell cycle, tube formation and the expression of Notch signaling-related proteins and mRNAs, and regulated miRNAs. After introducing Notch-1 siRNA and miRNA mimics, MDA-MB-231 cells presented with changes in miRNA levels, reduced Notch signaling-related proteins, and decreased tumor survival, invasion and angiogenesis. Conclusion: Luteolin inhibits Notch signaling by regulating miRNAs. However, the effect of miRNAs on the Notch pathway could be either Luteolin-dependent or Luteolin-independent. Furthermore, Notch-1 alteration may inversely change miRNAs levels. Our data demonstrates that Luteolin, miRNAs and the Notch pathway are critical in breast cancer development and prognosis.